2019
DOI: 10.1029/2018jd029297
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Algorithm to Estimate Latent Heating Rate Using Vertical Rainfall Profiles Over the Tibetan Plateau

Abstract: In this study, a simplified semiphysical retrieval algorithm for latent heat (LH) released from precipitation over the Tibetan Plateau is derived and analyzed. The physical basis of this algorithm is that the vertical gradient of rain rate (−dR/dZ or Γ) represents the temporal rate of rain formation based on the steady state assumption, and the precipitation formation rate is closely related to the cloud formation rate, which is directly proportional to the latent heating rate. In this algorithm, the LH rate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The enhanced valley wind across the Himalayas has also been found by previous studies with observations and numerical simulations (e.g., Egger et al, 2000;Zängl et al, 2001;Carrera et al, 2009;Karki et al, 2017;Lin et al, 2018). However, it is noteworthy that previous studies have found that the orographic drag (including gravity wave drag and turbulence orographic form drag) over a region with complex topography, such as the Himalayas and other mountainous areas, would weaken the overall near-surface wind speed (e.g., Beljaars et al, 2004;Horvath et al, 2012;Jiménez and Dudhia, 2012;Zhou et al, 2017Zhou et al, , 2018Lin et al, 2018;Wang et al, 2020). Therefore, the near-surface wind speed is also examined.…”
Section: Transport Flux Into the Tpsupporting
confidence: 83%
See 2 more Smart Citations
“…The enhanced valley wind across the Himalayas has also been found by previous studies with observations and numerical simulations (e.g., Egger et al, 2000;Zängl et al, 2001;Carrera et al, 2009;Karki et al, 2017;Lin et al, 2018). However, it is noteworthy that previous studies have found that the orographic drag (including gravity wave drag and turbulence orographic form drag) over a region with complex topography, such as the Himalayas and other mountainous areas, would weaken the overall near-surface wind speed (e.g., Beljaars et al, 2004;Horvath et al, 2012;Jiménez and Dudhia, 2012;Zhou et al, 2017Zhou et al, , 2018Lin et al, 2018;Wang et al, 2020). Therefore, the near-surface wind speed is also examined.…”
Section: Transport Flux Into the Tpsupporting
confidence: 83%
“…The goal of this study is to investigate the impacts of different representations of topography on the transport of BC across the Himalayas. Therefore, besides this control experiment, one sensitivity (idealized) experiment is also conducted with the same configuration as the control one except that the terrain heights of the inner domain at 4 km resolution are bilinearly interpolated from the terrain heights at 20 km resolution similar as previous studies (e.g., Shi et al, 2008;Wu et al, 2012b;Lin et al, 2018). The two exper- iments are referred to the simulations with the complex and smooth topographies, respectively, hereafter.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the warm and humid summer monsoon frequently reaches the steep southern slope of the QTP, making it conducive to the formation of unique cloud–precipitation distributions (Chen et al, ; Chen et al, ; Fu et al, ; Qie et al, ; Yan et al, ; Yan & Liu, ; Zhang et al, ). In particular, the southeastern QTP (SETP) exhibits high‐frequency convective cloud systems consisting of very high cloud cover and large‐areal precipitation (Kurosaki & Kimura, ; Li et al, ; Maussion et al, ; Tan et al, ; Tong et al, ; Yu & Fu, ), and is the source of many large rivers in Asia, including the Jinsha, Lancang, and Nujiang rivers (Tan et al, ). In addition, 26% of convective cloud systems over the QTP move eastward in summer (Hu et al, ), leading to frequent storm rainfall and floods in summer over eastern China (Tao & Ding, ; Yasunari & Miwa, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of observations from active and passive satellite instrumentation has enabled significant progress in the quantitative understanding of the horizontal and vertical spatial distribution of cloud systems over the southern QTP (Qie et al, ; Chen et al, ; Fu et al, ; Zhang et al, ; Chen et al, ; Yan & Liu, ; Luo et al, ; Li et al, ). For instance, Chen et al () revealed that the distribution of cloud top heights (CTH) gradually changes from bimodal (3 and 15 km) over the foothills of the Himalayas, to unimodal (7–9 km) over the QTP.…”
Section: Introductionmentioning
confidence: 99%